THE PLACE OF SOCIAL SECURITY IN THE SYSTEM OF NATIONAL SECURITY - Turaev O.B (PT. Antis International Publisher, 2025)
Objective: This study examines social security as an integral component of national security, analyzing the interconnections between individual, societal, and state interests in ensuring social stability. Method: The research employs a systematic approach, integrating sociological analysis to assess contemporary threats emerging within societal transformations. A qualitative methodology is used to evaluate policy frameworks and theoretical perspectives on social security. Results: The findings reveal that social security threats arise from economic instability, demographic shifts, and geopolitical tensions, necessitating comprehensive policy responses. The study identifies key vulnerabilities and proposes strategic measures to mitigate risks and enhance resilience. Novelty: Unlike previous studies that treat social security in isolation, this research provides a holistic perspective, positioning social security within the broader framework of national security. It highlights the evolving nature of threats in the modern socio-political landscape and underscores the need for adaptive strategies to safeguard social stability in dynamic environments.